Current findings on terrestrial plants – Engineered nanomaterial interactions: Are plants capable of phytoremediating nanomaterials from soil? - Delgado Ríos, Marcos (2018)
Engineered Nanomaterials (ENMs) are revolutionizing our daily lives, industry, and agriculture. Along with their novel applications, major concerns have emerged due to the potential toxicity to biological systems. Since soils are considered the main destination for ENMs, research focused on their interaction with plants is gaining more attention, especially at the physiological and biochemical levels. This review addresses the capacity of some plants to accumulate ENMs or released ions, highlighting the beneficial and detrimental effects and the potential use of some plants to remediate ENM-contaminated environments. Although the uptake process depends on multiple factors, the literature suggests that concentrations <50 mg/kg are beneficial, while higher doses negatively impact physiological and biochemical parameters. However, the current data does not allow the formulation of mechanistic model effects. Finally, this review remarks on the pivotal role played by plants as a sustainable alternative to face the environmental buildup of ENMs and to guarantee food security.